2015
DOI: 10.1002/pon.3768
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cancer, satisfaction with care, emotional distress, and adjustment to illness: an Italian multicenter study

Abstract: Most cancer patients were fully informed about their diagnosis, although awareness of disease was not coincident with awareness of prognosis and disease progression. Information and knowledge were not destructive of hope and did not increase distress. Family issues are still a significant factor molding openness and sharing of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 50 publications
2
35
1
2
Order By: Relevance
“…In this present study, we found that 58.2 % of the advanced breast cancer outpatients assumed their treatment intent incorrectly; in other words, they believed that the treatment was meant to cure their cancer completely. In contrast with other researchers' comments, it seems that the perceived curability of illness has not improved with respect to the past [10]. This finding may be a result of the medical characteristics of our sample.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In this present study, we found that 58.2 % of the advanced breast cancer outpatients assumed their treatment intent incorrectly; in other words, they believed that the treatment was meant to cure their cancer completely. In contrast with other researchers' comments, it seems that the perceived curability of illness has not improved with respect to the past [10]. This finding may be a result of the medical characteristics of our sample.…”
Section: Discussioncontrasting
confidence: 85%
“…Recently, Costantini et al classified 51 % of the total patients with metastatic cancer as having good awareness of prognosis (perceived low curability of disease) [10]. In a different study that was conducted with 147 patients with metastatic cancer in Italy, 72.4 % of the patients did not have appropriate awareness of prognosis [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Costantini et al . ). Indeed, satisfaction with the kind of information provided has previously been associated with a more positive perception of the disease, and may correlate with improved disease outcomes and improved quality of life (Husson et al .…”
Section: Discussionmentioning
confidence: 97%
“…35 Satisfaction with knowledge and/or increased knowledge, are not associated with distress, [36][37][38][39][40] so high quality communication strategies that employ all aspects of the PCC model may be necessary to decrease distress, 21,41 for example discussion of faith and spirituality. 42…”
Section: Discussionmentioning
confidence: 98%